Ultrafast Plasmonic Nanoantenna-ITO Hybrid Switches - Martina Abb; Otto L. Muskens (International Journal of Optics)
We present here a new type of device using nonlinear hybrid antenna-semiconductor (ITO) interaction. We observe a picosecond transient response from the antenna that cannot be explained by either pure ITO or antenna nonlinearities independently. We study the dependence of the hybrid interaction on several experimental parameters, including the polarization of excitation and detection.